Body shots : early cinema's incarnations - Auerbach, Jonathan, 1954- (Berkeley : University of California Press, 2007)
Argues that it was the human form in motion that most profoundly shaped early cinema. Situating his discussion in a political and historical context, the author begins his analysis with films that reveal striking anxieties and preoccupations about persons on public display. It also considers twentieth-century American incarnation of cinema itself.
Body, movement, space -- Looking in: McKinley at home -- Looking out: visualizing self-consciousness ; Interlude: the vocal gesture: sounding the origins of cinema -- Chasing film narrative -- Windows 1900; or, Life of an American fireman -- The stilled body.
Includes bibliographical references (pages 179-193) and index.
Print version record.
English.
JSTOR
Keywords: Human body in motion pictures; Silent films -- History and criticism; Corps humain au cinéma.; Films muets -- Histoire et critique; PERFORMING ARTS -- Film & Video -- Reference; PERFORMING ARTS -- Film & Video -- General; Human body in motion pictures; Silent films; 19th century american film history; 20th century american film history; american film; american fireman; bodies in public; bodies in space; cinema of attractions; cinema production; cinema; corporeal movement; early cinema; film history; film narrative; film studies; film; human form in motion; movie history; movie studies; movies; persons on public display; presidential candidate; self consciousness; visual art; visual spectacle; william mckinley; Criticism, interpretation, etc